Behavior and Control of the Ballastless Track-Subgrade Vibration Induced by High-Speed Trains Moving on the Subgrade Bed with Mud Pumping - Junjie Huang; Qian Su; Ting Liu; Wei Wang (Shock and Vibration)
This paper investigates behavior and control of the ballastless track-subgrade vibration induced by high-speed trains under mud pumping occurring in the subgrade bed. The characteristics of mud pumping occurring in the subgrade bed under the ballastless track structure are analyzed by visual observation and nondestructive testing. Then, based on the injection of the low-viscosity epoxy resin (LVER), the repair procedures for the mud pumping are proposed. A variety of on-site tests are performed on the ballastless track-subgrade with and without mud pumping and also after mud pumping reinforcement to analyze the vibration of the ballastless track-subgrade under the high-speed trains. The test results show that mud pumping can significantly increase the vertical vibration acceleration and displacement of the ballastless track structure and slightly decrease the vibration of subgrade surface. After mud pumping reinforcement, the abnormal vibration of the ballastless track-subgrade can be effectively controlled to make the vibration close to normal. In addition, the vibration ratio of the subgrade surface to the concrete base is proposed as a way to evaluate the effectiveness of the reinforcement of the mud pumping using the LVER, based on the vibration attenuation feature of the ballastless track-subgrade.